Scenarios of Potential Unconventional Security Threats as Public Policy Concern for Nepal - Upreti, Bishnu Raj (Journal of APF Command and Staff College, 2023)
This paper is about drawing different scenarios of potential unconventional security threats in Nepal as a major public policy concern. However, not much work has been done so far in this issue so far and therefore need greater attention. The aim of this paper is to draws different potential unconventional security threats in Nepal. While analyzing the unconventional security challenges, I have used the analytical formwork of four conceptual parameters like a) Understanding and commitment of domestic actors, b) domestic coping capacity, c) external geo-strategic interests and d) Sudden devastations and natural calamities. Based on these parameters I have drawn three different scenarios of unconventional security and consequent security risks. The methods used to collect primary and secondary data were observation, content analysis, in-depth interviews and literature review. This paper concludes that unconventional security situation depends on domestic coping capacity, commitment of policy decision makers, degree and intensity of external geo-strategic, political, economic, and other security interests and frequency and degree of natural calamities. The paper concludes that Nepal is in potentially high risks of unconventional security challenges and national unity is essential to handle with the future potential unconventional challenges.